The Effect of Performance Assessment and Work Discipline on the Work Productivity of Inpatient Installation Nurses at Performancelaran Cianjur Hospital - Fadya Maulani Laila; Mochamad. Vrans Romi (LP2M IAIN Palopo, 2026)
Nurses' work productivity is one of the important indicators in determining the quality of hospital services. Optimal productivity levels will support the effectiveness of health services, increase patient satisfaction, and strengthen organizational performance. However, nurses' work productivity is influenced by various factors, including performance assessment and work discipline. This study aims to analyze the effect of performance assessment and work discipline on the work productivity of nurses in the Inpatient Installation of Pagelaran Cianjur Hospital, both partially and simultaneously. The research uses a quantitative approach with the explanatory survey method. The research population is all nurses of the Inpatient Installation of Pagelaran Cianjur Hospital which totals 34 people. The sampling technique uses saturated sampling, so that the entire population is used as a research respondent. Data is collected through the deployment of questionnaires that have been tested for validity and reliability. Data analysis was carried out using multiple linear regression analysis with the help of IBM SPSS Statistics which included classical assumption tests, determination coefficients, partial tests (t test), and simultaneous tests (F tests). The results of the study showed that performance appraisal had an effect on the work productivity of nurses. Work discipline also affects the work productivity of nurses. In addition, simultaneous performance assessment and work discipline have a significant effect on the work productivity of nurses in the Inpatient Installation of Pagelaran Cianjur Hospital. These findings show that increasing nurses' work productivity can be achieved through the implementation of an objective, transparent, and employee-development-oriented performance appraisal system, as well as supported by improving work discipline through compliance with regulations, punctuality, and responsibility in carrying out duties. The results of the research are expected to be considered for the management of Pagelaran Cianjur Hospital in developing human resource management policies that are able to increase the work productivity of nurses and the quality of health services to the community.